ANALISIS EFEKTIVITAS DAN KONTRIBUSI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN NAGEKEO - Rua, Skolastika Febronia Menge; De Rozari, Petrus Emanuel; Tameno, Nikson (RJABM (Research Journal of Accounting and Business Management), 2023)
This study aims to determine whether the collection of Fees for Acquisition of Rights on Land and Buildings (BPHTB) is effective and contributes to Local Original Revenue and Local Taxes of Nagekeo Regency, especially from 2017 to 2021 by analyzing these two variables and the causes of the decline in BPHTB targets, especially from 2019 to 2020. This type of study is a combination research method (Mix Methods) with a Sequential Explanatory model conducted through a case study. Data collection techniques using documentation and interviews. The result of this study is the level of effectiveness of the Fees for Acquisition of Rights on Land and Buildings (BPHTB) during 2017-2021 has an average effectiveness value of 120.71% which is considered very effective. In 2019-2020 the effectiveness criteria dropped to be quite effective because it was achieved less than 90%. The contribution of the Fees for Acquisition of Rights on Land and Buildings (BPHTB) to the Local Original Revenue (PAD) of Nagekeo Regency during 2017-2021 has an average contribution of 0.40% which in the calculation is interpreted as "very less" because BPHTB is a small part of local taxes which are district/city taxes which when compared to PAD, BPHTB has a very small proportion of contribution. Likewise, the contribution of BPHTB to local taxes has an average contribution of 3.10% which has very insufficient criteria. Because the amount of BPHTB revenue depends on the taxpayer who submits the transfer of land / building rights whose NJOP is above the standard NPOPTKP value of Rp.60,000,000. To increase the contribution and effectiveness of BPHTB, the government is expected to make adjustments to the Tax Object Sale Value (NJOP) by establishing a regional head regulation (Perkada) on land price standards. Establish cooperation with the head of the KPKNL office, BPN in Nagekeo Regency and Notary PPAT.